The new liberalism: Trade policy developments in emerging markets - Zdenek Drabek; Sam Laird (World Trade Organization (WTO), 1997)
In the last ten years, there has been a sea change in trade and related policies in emerging markets. This results from autonomous reforms undertaken in conjunction with macro-economic stabilization programmes. Many non-tariff measures have been eliminated and tariffs, now the principal trade instrument, have been rationalized and reduced. Considerable increases in security of market access result from increased membership of the GATT/WTO system, which itself underwent important changes as a result of the Uruguay Round, further developed in the first Ministerial Meeting of the WTO in Singapore in December 1996. The systemic changes and the expansion of WTO membership to the transition and other economies mark a dramatic change in international economic relations.
Keywords: F01; F02; F13; 330; trade liberalization; WTO; GATT; emerging markets